For children with developmental disabilities Practical research to establish effective learning method - Nakamura, Takahiro (Journal of Learning Analytics, 2021)
In order to establish a learning guidance method for children with developmental disabilities, we clarified effective educational methods and learning support methods for these children through comparison of various teaching materials. The participants were 40 second-year junior high school students, whose IQs were around 70. In this paper, compared the differences in learning results between ICT teaching materials (video teaching materials) and descriptive teaching materials (paper media). These students were randomly assigned to one of the four groups. In the two of these groups the students learned ICT (video) materials; in the other two groups paper-and-pencil materials were used. The students have learned math and Japanese in a 45-minut class twice a week for one year. Based on the scores of monthly tests and the number of problems the students worked through, it is concluded that the print-type, paper-and-pencil materials, which can be solved in 5 to 10 minutes, were most effective.